2004
DOI: 10.17660/actahortic.2004.654.14
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Acquisition of Plant Related and Environmental Parameters (Plant Monitoring) in Gerbera: Determining Plant Responses

Abstract: For on-line plant monitoring equipment to be functional in commercial glasshouse horticulture, relations between sensor readings and plant responses on both the short (days) and long term (weeks) are required. For this reason, systems were installed to monitor rockwool grown gerbera plants on a minute-to-minute basis from July 2002 until April 2003. Data collected included, amongst others, crop transpiration from lysimeter data (2 m 2 ), canopy temperature using infrared sensors, rockwool water content, and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Since these studies were conducted using deep-flow culture conditions with the roots free from the growth media, it was easier to measure the crop weight and roots with the load cells. However, compared to previous studies with roots fixed in growing media or soils [13,14], our experimental system showed high accuracy and proved its suitability for measuring the fresh weight of bell peppers in soilless cultures.…”
Section: Continuous Changes In Fresh Weight and Its Verificationmentioning
confidence: 63%
See 1 more Smart Citation
“…Since these studies were conducted using deep-flow culture conditions with the roots free from the growth media, it was easier to measure the crop weight and roots with the load cells. However, compared to previous studies with roots fixed in growing media or soils [13,14], our experimental system showed high accuracy and proved its suitability for measuring the fresh weight of bell peppers in soilless cultures.…”
Section: Continuous Changes In Fresh Weight and Its Verificationmentioning
confidence: 63%
“…This technique is not applicable for soilless cultures of bell peppers using solid growing media, where the moisture content of growing media changes continuously from irrigation, drainage, and crop water uptake. Baas and Slooweg [13] installed a compressive load cell under gerbera-planted rockwool media, and used frequency domain Agronomy 2019, 9, 652 2 of 13 reflectometry (FDR) sensors, which measured the volume of moisture in the growing media using permittivity, to calculate crop fresh weight by excluding the moisture weight of growing media. This method can be used to calibrate the moisture weight of growing media as it changes continuously throughout the day, but this method can only be applied to crops' gravitational weight.…”
Section: Introductionmentioning
confidence: 99%
“…After the end of each irrigation event, the system records the actual weight of the whole plant-substrate-container system; the user must set the maximum value of weight loss (the net irrigation volume) after which a new irrigation event will start. In the literature different examples of plant weighing systems are reported for tomato (Takaichi et al, 1996), gerbera (Baas and Slootweg, 2004), cucumber and tomato (CropAssist®, Helmer et al, 2005), Boston and coral lettuce (Chen et al, 2016). The system is very good for small potted plants, while some problems are encountered when it is applied to species with large or tall canopies: in all these cases, the oscillation of the plant canopy can result in an unstable and erroneous measurement of the plant weight.…”
Section: Weighing Systemmentioning
confidence: 99%
“…However, the instrument can only be applied in the laboratory, as it requires two electronic balances to measure a single plant’s weight. Baas and Slootweg (2004) developed an on-line plant monitoring equipment for horticulture, which measures the weight of a group of Gerbera using multiple load cells. A group of Gerbera was growing on the Rockwool slab.…”
Section: Introductionmentioning
confidence: 99%
“…A group of Gerbera was growing on the Rockwool slab. The weight system mounted with load cells was put under the Rockwool slab to automatically measure the total weight of plants ( Baas and Slootweg, 2004 ). This instrument achieves automated plant weight measurements in real cultivational space; however, it can only measure the total weight of a group of Gerbera, not a single plant’s weight.…”
Section: Introductionmentioning
confidence: 99%